Oral spray wintertime vitamin D3 supplementation has no impact on inflammation in Gaelic footballers. (5th October 2016) - Todd, J. J.; McSorley, E. M.; Pourshahidi, L. K.; Madigan, S. M.; Crowe, W.; Laird, E. J.; Healy, M.; McNeilly, A.; Magee, P. J.
Abstract : Vitamin D inadequacy [total 25(OH)D <50 nmol/L] is widespread in athletes. The biologically active metabolite, 1, 25‐dihydroxyvitamin D, may be involved in regulating inflammation although in vitro findings have not been consistently replicated in human intervention trials. This study, conducted at a latitude of 55°N, aimed to assess inflammatory biomarkers in Gaelic footballers before and after a wintertime vitamin D3 intervention. Samples from a 12‐week double‐blind, randomized, placebo‐controlled trial, in which 42 Gaelic footballers received 3000 IU (75 μg) vitamin D3 daily or placebo via oral spray solutions, were analysed for a range of inflammatory biomarkers. Cytokines (interleukin‐8 and tumor necrosis factor‐α), cathelicidin and high sensitivity C‐reactive protein were quantified by multiplex assay, enzyme‐linked immunosorbent assay and clinical biochemistry, respectively. White blood cell, lymphocyte, and neutrophil concentrations were determined by full blood profile. Data on total 25‐hydroxyvitamin D, measured by LC‐MS/MS, were available from the previous study. Vitamin D3 supplementation significantly increased mean total 25‐hydroxyvitamin D concentrations from 47 to 84 nmol/L ( P  = 0.006); yet this had no effect on white blood cell count ( P  = 0.699), lymphocyte ( P  = 0.694), neutrophil ( P  = 0.594), interleukin‐8 ( P  = 0.334), tumor necrosis factor‐α ( P  = 0.587), cathelicidin ( P  = 0.745) or high sensitivity C‐reactive protein concentration ( P  = 0.621) compared to placebo. 12‐weeks vitamin D3 supplementation did not impact the immune profile of Gaelic footballers. This is likely because biomarkers were within their respective normal range or at a concentration similar to that of the general population at baseline. Future studies are encouraged to use inflammation as their primary outcome measure and recruit athletes at risk of compromised immunity.